First man [videorecording (DVD)] - Gosling, Ryan, 1980-; Foy, Claire, 1984-; Clarke, Jason, 1969-; Hansen, James R. (Universal Pictures Home Entertainment, 2019)
The riveting story behind the first manned mission to the moon, focusing on Neil Armstrong and the decade leading to the historic Apollo 11 flight. A visceral and intimate account told from Armstrong's perspective, based on the book by James R. Hansen, the film explores the triumphs and the cost, on Armstrong, his family, his colleagues and the nation itself; of one of the most dangerous missions in history.